Managing elections - who does it better? A comparative analysis of election regulators in Malaysia and the United Kingdom - Singh, Arwyn (2014)
This paper reviews the management of elections in Malaysia and the United Kingdom by the countries’ respective election regulators.In examining the fairness of the current framework in Malaysia, the role of the election regulator, its independence and impartiality will be scrutinized.The author will review the relevant provisions of the Federal Constitution and the electoral laws together with media resources (print and electronic) in analyzing the management of elections in Malaysia. The author will also compare the election regulator of Malaysia with that of the United Kingdom, and conclude with recommendations towards a new structure for the management of elections in Malaysia.